The parallel texts of the film text - Al Quraishi, Khdair Abyes Jyyad (Al-Adab Journal, 2019)
The texts parallel to the original text are of importance in being the thresholds for the entry of the original text, and add to the text how much information and knowledge, and if the studies came to look at the written texts, and in the approaches between the film text and other texts, we find the parallel texts of the film (poster, title, The first chapter, which contained the methodological framework of the research. The problem of the research was the following question: How can the parallel texts be good thresholds to enter the worlds of text? The aim of the research also included the disclosure of these parallel texts The second chapter / theoretical framework on two subjects was first titled (text and film text), which dealt with the concepts of text and film text and parallel texts, while the second section (parallel texts of the film text) came looking at the parallel texts of the film text. The third chapter included the research procedures. The fourth chapter came to practical application of the parallel texts. The research also included the results of the research